Habitat preferences and feeding behavior of speckled mousebird (Colius striatus) in urban Cameroon - Dorvald Nice Domeni; Taku Awa; Solange Mekuate Kamga; José Innoncent Tamdjo Tache; Jan Riegert (Academia Environmental Sciences and Sustainability)
Forests and other intact areas within the tropics are nowadays in the primary focus of researchers, while little or no attention is paid to urban sub-Saharan environments, justifying the need to gather baseline data. It is important to understand urban bird species ecology and uncover its interactions with city people. The speckled mousebird (SM, Colius striatus) is one of the most common species in rural and urban areas within man-made environments and is endemic to sub-Saharan Africa. We systematically sampled 222 random count points in Dschang (West Cameroon) using binoculars within buffers of a 50 m radius around the count points for 10 min, two times during the period of September–November 2022. The population density reached 1.33 ind./ha, and its distribution largely followed a random pattern. The presence of SM was positively correlated with the abundance of fruiting trees, with the most important being the percentage of guava (Psidium guajava) and papaya (Carica papaya) trees. Similarly, the presence of SM was positively linked to the size of human population, as it often occurred within mosaic agricultural areas and near dwellings. The percentage of feeding time increased around garbage sites due to the greater availability of nutrients for fruiting trees there. We further found a positive relationship between the percentage of feeding time and temperature, along with an increased number of vocal interactions around garbage sites. Our results showed that interactions between SM and humans were a significant driver of SM distribution within the study area.